2015
DOI: 10.1002/imhj.21521
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Mental Health Moderates the Relationship Between Oxytocin and Interactive Behavior

Abstract: Mothers with mood or anxiety disorders exhibit less optimal interactive behavior. The neuropeptide oxytocin (OT) has been linked to more optimal interactive behaviors in mothers without mental illness, and it may play a particularly beneficial role in mothers with mood or anxiety disorders given its antidepressant and anxiolytic functions. We compared the relationship between OT and interactive behavior in mothers with and without mental health problems. Participants included 20 women diagnosed with postpartum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 81 publications
(126 reference statements)
0
13
0
Order By: Relevance
“…Blockage of OTRs within the medial PFC of rats prevents the normal attenuation of maternal anxiety and increases maternal aggressive behavior (Sabihi et al 2014). In human studies, higher ante-or postpartum endogenous OT levels have been found associated with positive maternal caregiving behavior, mother-infant bonding, and maternal attachment behavior, particularly in women with more psychosocial stress and anxiety (Strathearn et al 2012;Zelkowitz et al 2014;Samuel et al 2015). However, the normal association between higher peripartum endogenous OT secretion and positive parenting was found disrupted in mothers with adverse childhood experiences (Julian et al 2018).…”
Section: The Oxytocinergic System In the Peripartum Periodmentioning
confidence: 99%
“…Blockage of OTRs within the medial PFC of rats prevents the normal attenuation of maternal anxiety and increases maternal aggressive behavior (Sabihi et al 2014). In human studies, higher ante-or postpartum endogenous OT levels have been found associated with positive maternal caregiving behavior, mother-infant bonding, and maternal attachment behavior, particularly in women with more psychosocial stress and anxiety (Strathearn et al 2012;Zelkowitz et al 2014;Samuel et al 2015). However, the normal association between higher peripartum endogenous OT secretion and positive parenting was found disrupted in mothers with adverse childhood experiences (Julian et al 2018).…”
Section: The Oxytocinergic System In the Peripartum Periodmentioning
confidence: 99%
“…Such supportive behavior is reduced in mothers with depressive symptoms (33). Anxious mothers behave less appropriately (39) and are more open to misinterpretations of children’s cries, which may then lead to inappropriate reactions (40). Also, repeating sorrowful thoughts can lead to lower structuring during mother–child interactions (26, 4143).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Moreover, there are a handful of experimental studies using a neuro-ethological model [70], and some recent studies on the oxytocin gene (OXTR [71]) that point to the potentially powerful role that central and peripheral oxytocin could have on infant development. Two important issues that have been discussed across these studies are: (i) whether the most meaningful measure of oxytocin levels is peripheral, central or genetic and (ii) whether baseline or stimulus-linked measures of oxytocin are more reliable and valid approaches for studying individual differences [67].…”
Section: (B) Oxytocinmentioning
confidence: 99%
“…Thus, our work and others' demonstrates the interactive effects of infant neurohormones. Furthermore, the persistence of this relationship for cortisol [45,53] ( principally for infants of depressed mothers) and the diverging effect for peripheral oxytocin on mothers [67,76] and infants [73] have been documented, though questions endure. So while environmental stressors like maternal depression and anxiety along with cortisol reactivity confer risk, oxytocin (released in response to skin-to-skin contact, maternal affectionate touch and breastfeeding) buffers that risk by impacting infant brain development and their own behavioural and neurobiological regulation.…”
Section: (B) Oxytocinmentioning
confidence: 99%